Bioaccumulation of persistent organic pollutants in tissues of the Greenland shark Somniosus microcephalus from NE Greenland - CORSOLINI, SIMONETTA (2012)
The Greenland shark Somniosus microcephalus was indexed as near threatened by the IUCN Red List of Threatened Species in 2012. It is an interesting species from an ecotoxicologiacl point of view being a long-lived and slow-growing deep-sea shark. Population dynamics, biology, and life cycle knowledges are still limited as well as ecotoxicological data. The aims of this study were to determine the POP concentrations in tissues (red and white muscle, brain, gonad, fat, liver) by gaschromatography, and the dioxin-like compound Toxic Equivalents (TEQs) using the TEF method in order to assess the possible risk for the analyzed specimens. The persistent organic pollutants (POPs) studied were: polychlorobyphenils (PCBs), polychlorodibenzo-dioxins and -furans (PCDDs/DFs), polybromodiphenylethers (PBDEs). Three specimens of Greenland shark were captured by line in the Kong Oscar Fjord, Greenland Sea (North-East Greenland National Park) in August 2010, during the scientific expedition TUNU-IV in the framework of the international program TUNU-MAFIG (University of Tromsø). PCBs and PBDEs were detected in most of the samples and ranged 2.01-103 ng/g wet wt and 7.9-3050 pg/g wet wt, respectively. PCDDs/Fs were below the limit of detection in most of the samples, but showed unexpected high values when detected. The TEQ concentration (=TEQ_PCB+TEQ_PCDDs+TEQ_PCDFs) was 4.54 pg/g wet wt in white muscle; this value was higher that those found in soma bone species from the same area and the Mediterranean Sea. The Greenland shark may be at high ecotoxicological risk due to its longevity and food habits that may allow them to bioaccumulate toxic and persistent contaminants.